Drug adverse effects in HIV-infected patients receiving antiretroviral therapy-a pharmacovigilence approach - Gaula, M. D. (University of Limpopo ( Medunsa Campus), 2011)
Most pharmaceutical agents can result in side effects and toxicities that in some instances may be life threatening, especially if there is delay in their recognition. For various reasons it is therefore imperative to study adverse events associated with antiretroviral agents (ARVs). The aim of this study was to study the adverse events in adult HIV-infected patients receiving antiretroviral therapy at a public health treatment site, and to quantify the frequency of adverse events in different population subgroups. A retrospective cohort study was conducted in a sample of 99 patients (i.e. 70% females and 30% males) from a public health clinic providing antiretroviral drugs to more than 1500 patients. The reported adverse events were neurological disorders (33%), rash (17%), gastrointestinal toxicity (16%), lactic acidosis (14%), hepatitis (7%), lipodystrophy (7%), pancreatitis (5%), IRIS (3%), anaemia (1%), and gynaecomastia (1%). Based on the analysis of the presented data in this report, age, weight, gender, and pCD4 count are not the predictors for the development of lactic acidosis, pancreatitis, and peripheral neuropathy. The duration of treatment was found to be the predictor for the development of lactic acidosis, pancreatitis, and peripheral neuropathy in this study sample. More frequent and closer monitoring of the reported adverse events will be necessary for patients treated longer on ART. Information bias is possible as case data for all reported adverse effects were collected retrospectively from hand-written patient records which were not consistent and standardised.
Thesis (M Med Pharmacy)--University of Limpopo, 2011
Keywords: Antiretroviral agents (ARV)